Pengaruh Senam Nifas Terhadap Involusi Uteri Pada Ibu Nifas - Jehaut, Maria Kartini; Sukamto, Edi; Siregar, Nursyahid (POLTEKKES KEMENKES MANADO, 2024)
Background: There were 2 postpartum maternal deaths in Mahakam Ulu district caused by bleeding. Bleeding does not occur if uterine involution is going well. One of the factors that influences the uterine involution process is postpartum exercise. Objective: This research determines the effect of postpartum exercise on uterine involution in postpartum mothers at the Gate Sehat Mahulu RSP in 2023. Method: This type of research is Quasi Experimental with a pretest – posttest design with one group design. The research population was postpartum mothers with a sample size of 18 people. The data analysis used was the Wilcoxon test. Results: Based on the Wilcoxon test, the p value is 0.001 < α(0.05), indicating that there is an influence of postpartum exercise on uterine involution in postpartum mothers. Conclusion: There is an influence of postpartum exercise on uterine involution in postpartum mothers at the Gate Sehat Mahulu RSP in 2023